Wireless indoor antenna design for smart TV application / Hazman Haziq Sulaiman - Sulaiman, Hazman Haziq (2016)
This thesis presents a new indoor digital microstrip TV antenna in wireless connection. A Rectangular Microstrip Patch Antenna for lower UHF (ultra high frequency) incorporated with a single Slotted Complementary Split Ring Resonator (SCSRR) on the partial ground plane has been designed. The microstrip antenna is designed using CST2015 Simulation Software. The antenna designed is specific to 566 MHz with bandwidth of 357 MHz. A single SCSRR is used as a miniaturization technique to reduce the size of the microstrip antenna that can be applied in lower UHF especially in DTV broadcasting frequencies in Malaysia. The antenna design was limited to a size of 20.1 cm x 21.2 cm using FR-4 substrate with thickness 1.6mm and dielectric constant of 4.3. The performance of the designed antenna in terms of return loss, VSWR, radiation pattern, HPBW and line impedance at four frequencies; 478 MHz, 566 MHz, 606MHz, and 742 MHz was analyzed. The proposed antenna can be considered to achieve the objective based on the simulation and measurement results.